Konsep Pendidikan: Kajian singkat menurut perspektif Anies Rasyid Baswedan - Gultom, Adelia Angelia; Halimah, Nur; Rantina, Meilanta; Santoso, Gunawan (Yayasan Aya Sophia Indonesia, 2023)
The goal of this research is to find out the thoughts and perspectives of Anies Rasyid Baswedan from the SDIT AL MU'MIN TV YouTube channel entitled